Novel pathophysiological insights into CAR-T cell associated neurotoxicity - Vassilis Genoud; Vassilis Genoud; Denis Migliorini; Denis Migliorini; Denis Migliorini; Denis Migliorini (Frontiers in Neurology, 2023)
Chimeric antigen receptor (CAR) T cell therapy represents a scientific breakthrough in the treatment of advanced hematological malignancies. It relies on cell engineering to direct the powerful cytotoxic T-cell activity toward tumor cells. Nevertheless, these highly powerful cell therapies can trigger substantial toxicities such as cytokine release syndrome (CRS) and immune cell-associated neurological syndrome (ICANS). These potentially fatal side effects are now better understood and managed in the clinic but still require intensive patient follow-up and management. Some specific mechanisms seem associated with the development of ICANS, such as cytokine surge caused by activated CAR-T cells, off-tumor targeting of CD19, and vascular leak. Therapeutic tools are being developed aiming at obtaining better control of toxicity. In this review, we focus on the current understanding of ICANS, novel findings, and current gaps.